A bubble breakage model for finite Reynolds number flows. Issue 7 (3rd July 2017) - Solsvik, Jannike; Skjervold, Vidar T.; Jakobsen, Hugo A.
ABSTRACT: The breakage frequency of bubbles in turbulent liquid flows is modeled as the inverse of the breakage time by Martinez-Bazan et al. [J. Fluid Mech. 401: 157–182; 1999]. In this definition of the breakage frequency, it is assumed that the breakage probability is unity and hence all bubbles will break. This assumption is reasonable in turbulent flows at extremely high Reynolds numbers in which the turbulence energy dissipation is very high. For systems characterized by finite Reynolds numbers the energy dissipation rate decreases rapidly and the breakage probability is reduced significantly. In the present study, the breakage frequency model by Martinez-Bazan et al. has been extended to include the effect that only a fraction of the bubbles breaks at finite Reynolds numbers. For this model extension, an adjusted version of the breakage probability formula proposed by Coulaloglou and Tavlarides [Chem. Eng. Sci. 32: 1289–1297; 1977] was employed. The extended breakage frequency model for finite Reynolds number flows has been evaluated by comparison to recent experimental single bubble breakage data. It can be concluded that extensive experimental analyses are required to gather sufficient experimental data for improved understanding of the physical phenomena and for model validation. In particular, the bubble breakage analysis must be performed simultaneously with the characterization of the local turbulence properties in the flow. GRAPHICAL ABSTRACT: